“Como podemos nos articular melhor?”: A relação gestão/serviços na esfera municipal do SUS - Duarte, Fernanda Flores (2020)
Uncertainties in health sector management have challenged the application of SUS-derived principles. The National Humanization Policy proposes the strengthening of real-life analytical and practical competence, the encouragement of autonomy and the co-responsibility of the subjects. Thus, it is expected that managers, service professionals and users may form collaborative relationships enhancing democracy within health institutions. This inquiry focuses on practice within a municipal sphere of SUS and how one management team viewed its relationship with service professionals. The research follows qualitative principles, in which data was collected from focus groups composed of thirty-six representatives from health management teams in a municipality in SE Brazil. Analysis was carried out through the licensed software Iramuteq, which provides users with statistical analysis on text corpus and tables composed by individuals/words. Material from the collection produced a textual corpus submitted to the Descending Hierarchical Classification. After processing, five lines of inquiry were defined: 1. "Management: identity and daily tasks"; 2. "Territory, complexity, articulation and opportunities"; 3. "Conjectures and Expectation of management regarding Service Professionals"; 4. "Powers and Challenges of Meetings as Devices between Management and Services"; 5. "Metaphors on the Relationship between Management and Service Professionals". Drawing on the content of the classes shown above, it was found that the management group recognised the interdependence between themselves and the services team for the betterment of municipal health care. However, when characterising performance, managers are keen to mark the variation in task location. Terms such as "central" or "front-line" were frequently used to denote distance from service-delivery and even hierarchical opposition. Nevertheless, managers inclination towards a more horizontal structure was identified. Proceeding thus, institutional support, in-service training and linkage appearas aids both in favouring professional integration, and in strengthening the spirit of co-management. It was also shown that the existence of such space/arrangement does not guarantee the effectiveness of encounters, ability to collaborate, and the foundation of trest, among other elements necessary for professional cohesion. Weak distribution and poor upkeep of collective space were seen as challenges to integration, similarly the intensity and timespan of daily team management planning. Such unshared tasks devolve upon management. Also highlighted was the fragmented nature of the management team, where membership was difficult to identify Similar hindrances to integration, were teams' unfamiliarity with others' work, allied to a fragile appreciation of the actuality of a counterpart's sector.